Systematic transcriptome analysis associated with physiological and chronological aging in Caenorhabditis elegans - Ham, Seokjin; Kim, Sieun S.; Park, Sangsoon; Kim, Eun Ji E.; Kwon, Sujeong; Park, Hae-Eun H.; Jung, Yoonji; Lee, Seung-Jae V. (Genome Research, 2022)
Aging is associated with changes in a variety of biological processes at the transcriptomic level, including gene expression. Two types of aging occur during a lifetime: chronological and physiological aging. However, dissecting the difference between chronological and physiological ages at the transcriptomic level has been a challenge because of its complexity. We analyzed the transcriptomic features associated with physiological and chronological aging using Caenorhabditis elegans as a model. Many structural and functional transcript elements, such as noncoding RNAs and intron-derived transcripts, were up-regulated with chronological aging. In contrast, mRNAs with many biological functions, including RNA processing, were down-regulated with physiological aging. We also identified an age-dependent increase in the usage of distal 3′ splice sites in mRNA transcripts as a biomarker of physiological aging. Our study provides crucial information for dissecting chronological and physiological aging at the transcriptomic level.
10.1101/gr.276515.121